Empire records [videorecording (Blu-Ray)] - Heikkinen, Carol; LaPaglia, Anthony; Caulfield, Maxwell; Mazar, Debi; Cochrane, Rory; Whitworth, Johnny, 1975-; Tunney, Robin; Zellweger, Renée, 1969-; Embry, Ethan, 1978-; Tyler, Liv; Landrum, Bill; Landrum, Jacquie; et al. (Twentieth Century Fox Home Entertainment., 2018)
Crank it up another notch as a young group of misfits tackles another eventful day at their favorite indie record store. As they each cope with life's challenges, confront their fears, and learn what friendship is all about, they also must fight to save the Empire from being taken over by a soulless corporation.